Long-term survival in metastatic gastric cancer patient with Apatinib plus S-1 maintenance treatment following first-line chemotherapy—case report - Wang, Zhen; Li, Hao; Guan, Yue; Wu, Mingshuang; Hu, Manqing; Fang, Chenchen (Frontiers in Oncology, 2024)
AimGastric cancer is the third leading cause of cancer-related mortality and the fifth most common cancer globally. In China, many patients are diagnosed at an advanced stage and cannot be operated on, so the prognosis is very poor. The role of maintenance therapy after first-line chemotherapy in gastric cancer is still unclear. Apatinib is a small-molecule VEGFR-2 TKI and is currently approved for third-line treatment after failure of second-line chemotherapy for advanced gastric cancer. In this article, we use case reports to illustrate its effectiveness and to study what effective maintenance treatments are available for gastric cancer.MethodsThe main treatment is chemotherapy and targeted therapy. We reported a 68-year-old man with a diagnosis of advanced gastric cancer with liver metastasis. From 12/2014 to 05/2015 Oxaliplatin + S-1(dose) chemotherapy for 6 cycles, the efficacy of partial response (PR) evaluation. After the patient’s oral S-1 + Apatinib (dose) to maintain the therapeutic usage and dosage, the patient is well tolerated, the tumor is reviewed regularly, and the condition is stable. The patient was finally infected with the COVID-2019 in May 2023, resulting in death after ineffective treatment.ResultsAfter Oxaliplatin combined with S-1 regimen, the effect was up to PR. S-1 combined with Apatinib maintenance therapy after first-line chemotherapy, the patient has survived for more than 7 years without progression.ConclusionsThe current treatment of advanced gastric cancer is not satisfactory. The combined application of S-1 and Apatinib in gastric cancer maintenance therapy deserves further study. Maintenance therapy for gastric cancer has attracted wide attention, and more large-scale clinical research is under way.